Exploring the relationship between mental health and urban green space soundscapes: A scoping review - Elham Ahmadi; Sophia Baierl; Stephan Voss; Ida Asenkerschbaumer; Ursula Berndt; Leonie Bernhard; Anita Hennig; Anna-Lena Würfele; Michaela Coenen (PLoS ONE, 2026)
Urban soundscapes, particularly those experienced in green spaces, have been increasingly recognized as factors that influence human mental health. This scoping review explores the existing literature on soundscapes within urban green spaces and their associated mental health outcomes. It aims to classify the methodologies used in this domain, identify mental health outcomes related to urban green space soundscapes, and examine specific soundscape elements and their correlations with mental health. A systematic search of peer-reviewed studies was conducted. After screening titles, abstracts, and full texts, 22 studies met the inclusion criteria. Diverse methodological approaches were identified, with an emphasis on quantitative multi-method designs. Commonly studied mental health outcomes include stress reduction, mood enhancement, perceived restorativeness, and cognitive restoration. Standardized psychometric tools, such as the Perceived Stress Scale (PSS-14), Positive and Negative Affect Schedule (PANAS) and Perceived Restorativeness Soundscape Scale (PRSS) are frequently used as outcome measures. Natural soundscape elements such as birdsong, water sounds, and rustling leaves had a positive association with relaxation and perceived mental restoration throughout all studies, while mechanical sounds, such as traffic noise were linked to adverse mental health outcomes. These findings highlight that natural soundscapes in urban green spaces have a potential positive relationship with mental health by reducing stress and enhancing mood. However, the cross-sectional design and methodological heterogeneity of the included studies limit causal interpretation. Future research should explore multi-sensory experiences and examine soundscapes in diverse urban contexts to provide more robust insights into their relationship with mental health. The practical implications suggest that urban planners should prioritize integrating natural sound elements into urban areas to improve mental health. The study protocol of this scoping review had been registered at OSF (osf.io/4r7gd).